Anti-cancer Screening Of Some Transition Metal Ion Complexes With Coumarin Derivatives - Juliana Jumal; Dalal M. Ibrahim; Wedad Melad Al-Adiwish3 (Bendola Publishing, 2024)
In this study, an equal amount of -4-methyl-5,7-(bis pchlorophenyl azo) coumarin (ligand 6-hydroxy) and copper, cobalt, and nickel (metals) were reacted to synthesize the respective metal ion complexes. The synthesized metal complexes were characterized using various approaches such as CHN elemental analysis, 1H-NMR, mass spectral data, and FTIR. The outcome of the spectroscopic analysis showed the coordination of the ligand to the metal ion that is in the complexes through hydroxyl group; the data also showed the complexes to exhibit octahedral geometry. Further studies on the solid complexes were performed by molar conductance where all the synthesized metal complexes exhibited nonconductive properties in chloroform. An MTT-based cytotoxicity screening of the complexes against lung and breast cancer cells showed Co(II), Cu(II), and Ni(II) complexes to exhibit cytotoxic activity against the studied cells at low concentrations.